Endotoxin Tolerance Impairs IL-1 Receptor-Associated Kinase (IRAK) 4 and TGF-β-activated Kinase 1 Activation, K63-linked Polyubiquitination and Assembly of IRAK1, TNF Receptor-associated Factor 6, and IκB Kinase γ and Increases A20 Expression - Xiong, Yanbao (American Society for Biochemistry and Molecular Biology, 2011)
Endotoxin tolerance reprograms Toll-like receptor 4 responses by impairing LPS-elicited production of pro-inflammatory cytokines without inhibiting expression of anti-inflammatory or anti-microbial mediators. In septic patients, Toll-like receptor tolerance is thought to underlie decreased pro-inflammatory cytokine expression in response to LPS and increased incidence of microbial infections. The impact of endotoxin tolerance on recruitment, post-translational modifications and signalosome assembly of IL-1 receptor-associated kinase (IRAK) 4, IRAK1, TNF receptor-associated factor (TRAF) 6, TGF-β-activated kinase (TAK) 1, and IκB kinase (IKK) γ is largely unknown. We report that endotoxin tolerization of THP1 cells and human monocytes impairs LPS-mediated receptor recruitment and activation of IRAK4, ablates K63-linked polyubiquitination of IRAK1 and TRAF6, compromises assembly of IRAK1-TRAF6 and IRAK1-IKKγ platforms, and inhibits TAK1 activation. Deficiencies in these signaling events in LPS-tolerant cells coincided with increased expression of A20, an essential deubiquitination enzyme, and sustained A20-IRAK1 associations. Overexpression of A20 inhibited LPS-induced activation of NF-κB and ablated NF-κB reporter activation driven by ectopic expression of MyD88, IRAK1, IRAK2, TRAF6, and TAK1/TAB1, while not affecting the responses induced by IKKβ and p65. A20 shRNA knockdown abolished LPS tolerization of THP1 cells, mechanistically linking A20 and endotoxin tolerance. Thus, deficient LPS-induced activation of IRAK4 and TAK1, K63-linked polyubiquitination of IRAK1 and TRAF6, and disrupted IRAK1-TRAF6 and IRAK1-IKKγ assembly associated with increased A20 expression and A20-IRAK1 interactions are new determinants of endotoxin tolerance.